Cooperation among SMEs in Poland on path to their development - Siuda-Tokarska, Barbara (Managerial Economics, 2019)
On the basis of the overview of the literature of the subject, the signifi cance of the problem of cooperation among SMEs in the context of the factors infl uencing their development is presented. The author’s own empirical research conducted among the enterprises of the sector with and without foreign capital in Poland presents the engagement of these enterprises in cooperation with other enterprises as well as with other market entities such as local government units, research and development units, or institutions of higher education. The results of the research concerning various forms of cooperation among SMEs with other enterprises as well as the size classes of the cooperating enterprises are also graphically presented. Moreover, the assessment of the similarity of the structures of the SME sector enterprises with Polish and foreign capital is made, which in turn made it possible to defi ne their similarities and differences by taking into consideration their capital (Polish or foreign).